Effect of corrosion and fatigue on the remaining life of structures and its implication to additive manufacturing - Filippo Berto; Javad Razavi; Rhys Jones; D. Peng (Fracture and Structural Integrity)
This paper investigates the combined effect of corrosion and fatigue on the growth of cracks that arise from natural corrosion in steel bridges. It is shown that if these two effects need to be simultaneously analyzed. If not, then the resulting life is not conservative. Consequently, to enable a better understanding of the remaining life of structures this paper presents a simple methodology for performing this coupled analysis. The implication of this study to additively manufactured Ti-6Al-4V is also discussed.